The p150(Glued) CAP-Gly Domain Regulates Initiation of Retrograde Transport at Synaptic Termini. - Lloyd, T.E.; Machamer, J.; O'Hara, K.; Kim, J.H.; Collins, S.E.; Wong, M.Y.; Sahin, B.; Imlach, W.; Yang, Y.; Levitan, E.S.; McCabe, B.D.; Kolodkin, A.L. (Neuron, 2012)
p150(Glued) is the major subunit of dynactin, a complex that functions with dynein in minus-end-directed microtubule transport. Mutations within the p150(Glued) CAP-Gly microtubule-binding domain cause neurodegenerative diseases through an unclear mechanism. A p150(Glued) motor neuron degenerative disease-associated mutation introduced into the Drosophila Glued locus generates a partial loss-of-function allele (Gl(G38S)) with impaired neurotransmitter release and adult-onset locomotor dysfunction. Disruption of the p150(Glued) CAP-Gly domain in neurons causes a specific disruption of vesicle trafficking at terminal boutons (TBs), the distal-most ends of synapses. Gl(G38S) larvae accumulate endosomes along with dynein and kinesin motor proteins within swollen TBs, and genetic analyses show that kinesin and p150(Glued) function cooperatively at TBs to coordinate transport. Therefore, the p150(Glued) CAP-Gly domain regulates dynein-mediated retrograde transport at synaptic termini, and this function of dynactin is disrupted by a mutation that causes motor neuron disease.